A Review of Empirical Research on Global Talent Management. Issue 2 (June 2019) - Anlesinya, Alex; Dartey-Baah, Kwasi; Amponsah-Tawiah, Kwesi
Abstract: Global talent management as an academic field is regarded as a multi-disciplinary bridge field, which has recently emerged from the strategic international human resource management (HRM) and talent management fields as a critical strategic issue for multinational firms. While some literature reviews have been conducted on the topic, there is no systematic review of drivers, outcomes and challenges in empirical global talent management research. This study therefore provides a rigorous systematic review of empirical global talent management research from 2008 to 2017. The evidence reveals that global talent management can enhance multinational companies' global mobility outcomes, employer attractiveness, competitiveness and performance. However, challenges, such as huge financial costs, high rate of turnover among global talents, localization difficulties, corporate culture, and adjustment problems, of expatriate spouses can undermine the effectiveness of global talent management practices and programmes. Furthermore, the findings indicate that the qualitative approach and cross-sectional design have dominated empirical research on the topic while only few studies have performed multi-level analysis. The findings urge stakeholders to adopt a more holistic and well-informed view while designing and implementing global talent management initiatives either as researchers or practitioners. It also implies that despite the substantial interest in global talent management, the field is still under-explored or under-researched. The study makes contribution by providing the first systematic review of empirical global talent management research.